2021
DOI: 10.3390/ijms22084168
|View full text |Cite
|
Sign up to set email alerts
|

Aptamers for Anti-Viral Therapeutics and Diagnostics

Abstract: Viral infections cause a host of fatal diseases and seriously affect every form of life from bacteria to humans. Although most viral infections can receive appropriate treatment thereby limiting damage to life and livelihood with modern medicine and early diagnosis, new types of viral infections are continuously emerging that need to be properly and timely treated. As time is the most important factor in the progress of many deadly viral diseases, early detection becomes of paramount importance for effective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 221 publications
(232 reference statements)
0
36
0
Order By: Relevance
“…Aptamers might be used not only to treat the infection, but also to prevent it-viral infection can be inhibited in almost any step of the disease. Many studies confirmed that the most effective therapeutic strategy is to block the penetration of viruses into the cells and/or inhibition of enzymes involved in their replication (Figure 18) [94]. They are suitable subjects of structural modifications as in vivo biostability improvement and conjugation with other therapeutic molecules, such as s mall interfering RNA (siRNA) and ribozymes [95] [96].…”
Section: In Vitro Selex Methodsmentioning
confidence: 99%
“…Aptamers might be used not only to treat the infection, but also to prevent it-viral infection can be inhibited in almost any step of the disease. Many studies confirmed that the most effective therapeutic strategy is to block the penetration of viruses into the cells and/or inhibition of enzymes involved in their replication (Figure 18) [94]. They are suitable subjects of structural modifications as in vivo biostability improvement and conjugation with other therapeutic molecules, such as s mall interfering RNA (siRNA) and ribozymes [95] [96].…”
Section: In Vitro Selex Methodsmentioning
confidence: 99%
“…As possible strategies for therapy, aptamers may block the entry of viral particles into host cells by either competing with binding to host cell receptors or virus entry proteins [ 130 ]. On the other site, intracellular virus targeting by aptamers is also a promising strategy [ 131 ]. Aptamers were developed for blocking nucleocapsid assembly or targeting proteins involved in viral replication, such as SARS CoV NTPase/helicase [ 117 ], HIV reverse transcriptase [ 132 ], and hepatitis C virus (HCV) RNA polymerase [ 133 ], among other examples.…”
Section: From Aptamer Selection Towards In Vivo Applications Combating Virus Diseasementioning
confidence: 99%
“…In Table 1 , we briefly summarize the pros and cons of using aptamers for virus detection and inhibition when compared with antibody-based methods. 22 24 …”
Section: Introductionmentioning
confidence: 99%
“…Also, aptamers are quickly excreted by renal filtration from the bloodstream and thus need to be attached to other higher-molecular-weight molecules such as cholesterol or polyethylene glycol for prolonged bioavailability when used as diagnosis/imaging reagents or as part of drug complexes. In Table , we briefly summarize the pros and cons of using aptamers for virus detection and inhibition when compared with antibody-based methods. …”
Section: Introductionmentioning
confidence: 99%